Penyuluhan Gerakan 3M Plus dalam Upaya Pencegahan Demam Berdarah Dengue (DBD) pada siswa-siswi SDN 2 Denbatas - Devi, Natasha Pradnya; Saputra, Ni Putu Amy Restu Wahyuni; Daiva, Putu Rizky; Sudana, Vidya Aditi; Yuliyatni, Putu Cintya Denny (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Tabanan Regency in Bali Province has a DHF incidence rate of 137.01 cases per 100,000 population, increase from 2022 to 2023, which was 80.82 cases per 100,000 population. Therefore, prevention efforts are needed to increase knowledge about the importance of DHF prevention. This health promotion aims to increase knowledge, understanding and behaviour of dengue prevention among primary school students. Methods: Health promotion activities were conducted offline on Monday, 6 May 2024. The target group of this activity were students in grades 4-6 of SDN 2 Denbantas. PowerPoint slides and posters were used to attract the interest of the extension participants. The evaluation of the results was carried out qualitatively (enthusiasm of the participants) and quantitatively (pre- and post-test results). Results: The health promotion activity was attended by 47 participants. Participants were very active in the question and answer session. Based on the identity data on the pre/post test sheets, most participants were in grade 6 (38%) and female (53%). A total of 37 participants (79%) showed an increase in score, 8 participants (17%) had a fixed score and a total of 2 participants (4%) showed a decrease in score on the post-test. Conclusion: There was an increase in participants' knowledge, as well as participants' enthusiasm and activity in listening to the counselling materials. In future health promotion activities, educational videos or other interactive media can be used to make more interesting and provide a deeper focus on the message so it can be conveyed more effectively.